Home » Series » Page 3

Tag: Series

Test convergence of the series with an = 1/n if n odd and an = 1/n2 if n even

Test the series \sum_{n=1}^{\infty} a_n for convergence where the terms a_n are defined by

    \[ a_n = \begin{cases} \frac{1}{n} & \text{if } n \text{ is odd}, \\ \frac{1}{n^2} & \text{if } n \text{ is even}. \end{cases} \]


The series diverges.

Proof. (This proof might be overkill. You could simply observe that this series is greater than the sum of the reciprocals of the odd integers, and use limit comparison with \frac{1}{n}.)Using the piecewise definition of a_n we have

    \[ \sum_{n=1}^{\infty} a_n = \sum_{n=1}^{\infty} \left( \frac{1}{2n-1} + \frac{1}{(2n)^2} \right) = \sum_{n=1}^{\infty} \frac{4n^2 + 2n - 1}{8n^3 - 4n^2}. \]

Then using the limit comparison we have,

    \begin{align*}  \lim_{n \to \infty} \frac{ \frac{4n^2 + 2n - 1}{8n^3 - 4n^2}}{\frac{1}{n}} &= \lim_{n \to \infty} \frac{4n^3 + 2n^2 - n}{8n^3 - 4n^2} \\[9pt]  &= \frac{1}{2}. \end{align*}

Since we know \sum \frac{1}{n} diverges, the limit comparison test establishes the divergence of

    \[ \sum a_n. \qquad \blacksquare \]

Determine whether ∑ 1 / n1 + 1/n converges

Test the following series for convergence:

    \[ \sum_{n=1}^{\infty} \frac{1}{n^{1 + \frac{1}{n}}}. \]


The series diverges.

Proof. First, we write

    \[ \frac{1}{n^{1+\frac{1}{n}}} = \frac{1}{n \cdot n^{\frac{1}{n}}}. \]

Then, we know n < 2^n for all n \geq 1. (We can deduce this from the Bernoulli inequality, (1+x)^n \geq 1 + nx with x = 1. We proved the Bernoulli inequality in this exercise, Section I.4.10, Exercise #14.) Therefore, n^{\frac{1}{n}} < 2 and we have

    \[ \frac{1}{n \cdot n^{\frac{1}{n}}} > \frac{1}{2n}. \]

Since the series \sum \frac{1}{2n} diverges we have established the divergence of the given series

    \[ \sum_{n=1}^{\infty} \frac{1}{n^{1+\frac{1}{n}}}. \qquad \blacksquare\]

Determine whether ∑ ns((n+1)1/2 – 2n1/2 + (n-1)1/2) converges

Test the following series for convergence:

    \[ \sum_{n=1}^{\infty} n^s \left( \sqrt{n+1} - 2 \sqrt{n} + \sqrt{n-1} \right). \]


The series is convergent if s < \frac{1}{2} and divergent if s \geq \frac{1}{2}.

Proof. We will use the limit comparison test with series \sum \frac{1}{n^{\frac{3}{2} - s}} (which we know converges for s < \frac{1}{2} and diverges for s \geq \frac{1}{2}). First, we rewrite the terms in the series,

    \begin{align*}  \left|n^s \left( \sqrt{n+1} - 2 \sqrt{n} + \sqrt{n-1} \right) \right|&= n^s \left| \left( \frac{ \left( \sqrt{n+1} - 2\sqrt{n} + \sqrt{n-1}\right)\left(\sqrt{n+1} + 2 \sqrt{n} + \sqrt{n-1} \right)}{ \sqrt{n+1} + 2\sqrt{n} + \sqrt{n-1}} \right) \right|\\[9pt]  &= n^s \left| \left( \frac{2 \sqrt{n+1}\sqrt{n-1} - 2n}{\sqrt{n+1} + 2\sqrt{n} + \sqrt{n-1}} \right) \right| \\[9pt]  &= n^s \left| \left( \frac{2 \left( \sqrt{n^2 - 1} - n \right)}{2 \sqrt{n} + \sqrt{n+1} + \sqrt{n-1}} \right) \right|\\[9pt]  &= n^s \left| \left( \frac{2 \left( \sqrt{n^2 - 1} - n \right) \left( \sqrt{n^2-1} + n \right)}{\left( 2 \sqrt{n} + \sqrt{n+1} + \sqrt{n-1} \right) \left( \sqrt{n^2-1} + n \right)} \right) \right|\\[9pt]  &= n^s \left|\left( \frac{-2}{\left( 2 \sqrt{n} + \sqrt{n+1} + \sqrt{n-1} \right) \left( \sqrt{n^2-1} + n \right)} \right)\right| \\[9pt]  &= n^2 \left( \frac{2}{ \left( 2 \sqrt{n} + \sqrt{n+1} + \sqrt{n-1} \right) \left( \sqrt{n^2-1} + n \right)} \right). \end{align*}

Now, we can use the limit comparison test with \frac{1}{n^{\frac{3}{2} - s}}.

    \begin{align*}   & \lim_{n \to \infty} \frac{ n^s \left( \frac{2}{\left( 2 \sqrt{n} + \sqrt{n+1} + \sqrt{n-1} \right) \left( \sqrt{n^2-1} + n \right)} \right) }{ \frac{1}{n^{\frac{3}{2}-s}} } \\[9pt]  &= \lim_{n \to \infty} n^{\frac{3}{2}} \left( \frac{2}{\left( 2 \sqrt{n} + \sqrt{n+1} + \sqrt{n-1} \right) \left( \sqrt{n^2-1} + n \right)} \right) \\[9pt]  &= \lim_{n \to \infty} \frac{2}{\left( 2 + \sqrt{1 + \frac{1}{n}} + \sqrt{1 - \frac{1}{n}} \right) \left( \sqrt{1 - \frac{1}{n^2}} + 1 \right)} \\[9pt]  &= \frac{1}{4}. \end{align*}

(In the second to last line, we multiplied the numerator and denominator by n^{-\frac{3}{2}} and in the denominator we had n^{-\frac{3}{2}} = n^{-\frac{1}{2}}\cdot n^{-1} and split these two pieces between the two terms in the product of the denominator.) Therefore, the given series converges or diverges as \sum \frac{1}{n^{s-\frac{3}{2}}} does. Since \sum \frac{1}{n^{s - \frac{3}{2}}} converges for s < \frac{1}{2} and diverges for s \geq \frac{1}{2}, we have proved our claim. \qquad \blacksquare

Prove some properties of the sequence ean = an + ebn

Let \{ a_n \} and \{ b_n \} be two sequences that satisfy the relationship

    \[ e^{a_n} = a_n + e^{b_n} \]

for all n.

  1. Prove that if a_n > 0 for all n then b_n > 0 for all n.
  2. Prove that if a_n > 0 for all n and if \sum a_n is convergent, then

        \[ \sum \frac{b_n}{a_n} \qquad \text{converges}. \]


  1. Proof. Assume a_n > 0 for all n. From the given relation between the a_n and b_n we have

        \[ e^{a_n} = a_n + e^{b_n} \quad \implies \quad e^{b_n} = e^{a_n} - a_n. \]

    Now, we claim e^{a_n} - a_n > 1 for all n. To see this, consider the function

        \[ f(x) = e^x - x \qquad \implies \qquad f'(x) = e^x - 1. \]

    Since f'(x) > 0 for all x > 0 we have f(x) is increasing for all x > 0. Since f(0) = 1 we must have f(x) > 1 for all x > 0. Since a_n > 0 by assumption we then have

        \[ e^{a_n} - a_n > 1 \qquad \text{for all } n. \]

    But, this implies

        \[ e^{b_n} > 1 \quad \implies \quad b_n > 0 \]

    for all n. \qquad \blacksquare

  2. Proof. To prove \sum \frac{b_n}{a_n} converges we use the limit comparison test with \sum a_n. First, since \sum a_n converges we know

        \[ \lim_{n \to \infty} a_n = 0. \]

    Now, we use the given relation between the a_n and the b_n,

        \[ e^{a_n} = a_n + e^{b_n} \quad \implies \quad b_n = \log \left( e^{a_n} - a_n \right) = \log \left( 1 + \left( e^{a_n} - 1 - a_n \right) \right). \]

    Then, use the expansion of the exponential,

        \[ e^{a_n} = 1 + a_n + \frac{a_n^2}{2} + \cdots, \quad \implies \quad e^{a_n} - 1 - a_n = \frac{a_n^2}{2} + \frac{a_n^3}{6} + \cdots. \]

    This gives us

        \[ b_n = \frac{a_n^2}{2} + \frac{a_n^3}{6} + \cdots. \]

    Therefore,

        \begin{align*}  \lim_{n \to \infty} \frac{\frac{b_n}{a_n}}{a_n} &= \lim_{n \to \infty} \frac{b_n}{a_n^2} \\[9pt]  &= \lim_{n \to \infty} \frac{ \frac{a_n^2}{2} + \frac{a_n^3}{6} + \cdots }{a_n^2} \\[9pt]  &= \frac{1}{2} + \lim_{n \to \infty} \left( \frac{a_n}{6} + \cdots \right) \\[9pt]  &= \frac{1}{2}. &(\lim_{n \to \infty} a_n = 0.) \end{align*}

    Therefore, by the limit comparison test the series \sum \frac{b_n}{a_n} and \sum a_n either both converge or both diverge. Since \sum a_n converges by hypothesis, we have established the convergence of \sum \frac{b_n}{a_n}. \qquad\blacksquare

Prove or disprove two statements about absolute convergence

Prove or disprove the following two statements.

  1. If \sum a_n is absolutely convergent, then

        \[ \sum \frac{a_n^2}{(1+a_n^2)} \]

    is absolutely convergent.

  2. If \sum a_n is absolutely convergent, and if a_n \neq -1 for all n, then,

        \[ \sum \frac{a_n}{1+a_n} \]

    is absolutely convergent.


  1. Proof. Since \sum a_n converges absolutely, we know \sum |a_n| converges. By a previous exercise (Section 10.20, Exercise #50) we know that this implies that \sum a_n^2 converges. Then we have,

        \[ \frac{a_n^2}{1+a_n^2} \leq a_n^2 \]

    for all n since 1+ a_n^2 \geq 1. Hence, by comparison with \sum a_n^2 we have the convergence of

        \[ \sum_{n=1}^{\infty} \frac{a_n^2}{1+a_n^2}. \qquad \blacksquare \]

  2. Proof. Since \sum a_n converges absolutely, we know \sum |a_n| converges. Then, using the limit comparison test we have,

        \begin{align*}  \lim_{n \to \infty} \frac{|a_n|}{\left| \frac{a_n}{1+a_n} \right|} &= \lim_{n \to \infty} |1 + a_n| \\[9pt]  &= 1. \end{align*}

    The final equality follows since \sum a_n converges means we must have \lim_{n \to \infty} a_n = 0. Hence, the series \sum \left| \frac{a_n}{1+a_n} \right| converges; and thus,

        \[ \sum \frac{a_n}{1+a_n} \]

    converges absolutely (as long as a_n \neq -1 so that all of the terms are defined). \qquad \blacksquare

Prove that if ∑ an converges then ∑ (an)1/2 n-p converges for p > 1/2

Let \sum a_n be a convergent series of nonnegative terms (i.e., a_n \geq 0 for all n). Prove that

    \[ \sum \sqrt{a_n} n^{-p} \]

converges for all p > \frac{1}{2}. Provide an example to show this fails in the case p = \frac{1}{2}.


(Note. Thanks to Giovanni in the comments for pointing out the problems with the original proof.)

Proof. We apply the Cauchy-Schwarz inequality. (See this exercise for some more proofs regarding the Cauchy-Schwarz inequality.) The Cauchy-Schwarz inequality establishes that

    \[ \left( \sum_{n=1}^{N} b_n c_n \right)^2 \leq \left( \sum_{n=1}^{N} b_n^2 \right) \left( \sum_{n=1}^{N} c_n^2 \right). \]

So, to apply this to the current problem, we let

    \[ b_n = \sqrt{a_n}, \qquad c_n = \frac{1}{n^p}. \]

Then, since a_n \geq 0 we have a_n = |a_n|; hence, \left(\sqrt{a_n}\right)^2 = a_n. So, we have

    \begin{align*}  && \left( \sum_{n=1}^{N} b_n c_n \right)^2 &\leq \left( \sum_{n=1}^{N} b_n^2 \right) \left( \sum_{n=1}^{N} c_n^2 \right) \\[9pt]  \implies && \left( \sum_{n=1}^{N} \frac{\sqrt{a_n}}{n^p} \right)^2 &\leq \left( \sum_{n=1}^{N} a_n \right) \left( \sum_{n=1}^{N} \frac{1}{n^{2p}} \right) \\[9pt]  \implies && \left( \sum_{n=1}^{N} \frac{\sqrt{a_n}}{n^p} \right) & \leq \left( \sum_{n=1}^{N} a_n \right)^{\frac{1}{2}} \right) \left( \sum_{n=1}^{N} \frac{1}{n^{2p}} \right)^{\frac{1}{2}} \\[9pt]  \implies && \left( \sum_{n=1}^{N} \frac{\sqrt{a_n}}{n^p} \right) &\leq \left( \sum_{n=1}^{\infty} a_n \right)^{\frac{1}{2}} \left( \sum_{n=1}^{\infty} \frac{1}{n^{2p}} \right)^{\frac{1}{2}}. \end{align*}

But, on the right we know \sum a_n converges (by hypothesis) and we know \sum \frac{1}{n^{2p}} converges for p > \frac{1}{2}. Hence, each of the sums on the right converges, so the term on the right is some finite number M. This means the partial sums of \sum \frac{\sqrt{a_n}}{n^p} are bounded by a constant M. By Theorem 10.7 (page 395 of Apostol) this implies the convergence of the series

    \[ \sum_{n=1}^{\infty} \frac{\sqrt{a_n}}{n^p}. \qquad \blacksquare \]

Example. Let p = \frac{1}{2} and let a_n = \frac{1}{n \log^2 n}. Then, we know \sum a_n converges (by Example #2 on page 398 of Apostol, established with the integral test). However,

    \[ \sqrt{a_n} = \sqrt{n} \log n \quad \implies \quad \sqrt{a_n} \cdot n^{-\frac{1}{2}} = \frac{1}{n \log n}. \]

We know

    \[ \sum_{n=2}^{\infty} \frac{1}{n \log n} \]

diverges by the same example on page 398. Therefore, we conclude the theorem fails in the case p = \frac{1}{2}.

If ∑ |an| converges prove ∑ an2 converges

Prove that if the series \sum |a_n| converges then the series \sum a_n^2 also converges. Also, give an example to show that the converse is false, i.e., a case in which \sum a_n^2 converges but \sum |a_n| does not.


Proof. Assume \sum |a_n| converges. Then we know \lim_{n \to \infty} |a_n| = 0. Thus, by the definition of the limit, for all \varepsilon > 0 there exists an integer N such that

    \[ |a_n| < \varepsilon \qquad \text{whenever} \qquad n \geq N. \]

Taking \varepsilon = 1 we then know there exists an N such that

    \[ |a_n| < 1 \qquad \text{whenever} \qquad n \geq N. \]

But then, a_n^2 = |a_n|^2 < |a_n| if n \geq N. Thus, we have

    \[ \sum_{n=1}^{\infty} a_n^2 = \sum_{n=1}^N a_n^2 + \sum_{n=N+1}^{\infty} a_n^2. \]

The first sum is a finite sum so it converges, and the second sum converges by comparison with \sum |a_n|. Hence, \sum a_n^2 converges. \qquad \blacksquare

Counterexample. The converse is false. Let a_n = \frac{1}{n}. Then,

    \[ \sum_{n=1}^{\infty} a_n^2 = \sum_{n=1}^{\infty} \frac{1}{n^2} \]

converges. However,

    \[ \sum_{n=1}^{\infty} |a_n| = \sum_{n=1}^{\infty} \left| \frac{1}{n} \right| = \sum_{n=1}^{\infty} \frac{1}{n} \]

diverges.